An Assistive Haptic Interface for Robotic Teleoperation in Mixed Reality Environments - Carneiro, Sérgio; Vieira, Igor; Machado, Fabiana; Frizera Neto, Anselmo; Mello, Ricardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
Traditional 2D interfaces used in robot teleoperation frequently lack intuitiveness and depth perception, which can limit the effectiveness of human-robot interaction (HRI) in dynamic and complex settings. Addressing these challenges, this work presents a HRI system based on mixed reality and assistive haptic feedback for remote navigation. The proposed approach integrates a digital twin developed in Unity, connected to a real mobile robot via the ROS 2 middleware. The haptic interface, implemented using the Falcon Novint device, provides tactile feedback to the operator based on the detection of physical obstacles and virtual ones (simulated within the Unity environment). The system employs a detection ellipse to compute directional forces that assist the operator's decision-making during navigation without compromising their autonomy. The pilot study with four volunteers followed an experimental protocol that included familiarization and testing sessions, during which both objective and subjective data were collected to evaluate system performance, workload (NASA-TLX), and presence perception (PQ). The results indicated no collisions among participants, regardless of their familiarity with haptic technologies and virtual environments. The study provides relevant insights for optimizing, highlighting the benefits of assistive and immersive systems in promoting safety and user engagement in teleoperation tasks.